Menciptakan Good Governance Melalui Inovasi Pelayanan Publik di Kota Surakarta - Yohanitas, Witra Apdhi (Pusjar SKPP Lembaga Administrasi Negara, 2016)
Theoptimum performance of public services is essential in order to improve the competitiveness of the region and to realize good governance. The success of the development is determined by the implementation of the appropriate andthe right policies. Realizing the competitive climate as the embodiment of a conception of innovation is an integral part to the progress of a region. Therefore, the development ofinnovation’sculture as one aspect of a bureaucratic culture that is essential for the success of bureaucratic reform. The success of Surakarta in fostering innovation is the main attraction, despite the change of leadership. Innovative programs keep continuinglike surakarta public health care, child incentive cards, residence digital archive, One hour ID card service, and others. Cooperation with stakeholdersand the public create an innovative program that became the flagship and pride of the city government of Surakarta. Program planning and budgettingare supporting factor in the sustainability of public service improvement programs.Keyword:public service, innovation, Surakarta, innovative programs, good governanceKinerja optimal pelayanan publik sangat penting dalam rangka meningkatkan daya saing daerah serta mewujudkan penyelenggaraan pemerintahan yang baik. Keberhasilan dari pembangunan ditentukan oleh implementasi kebijakan yang benar dan sesuai. Mewujudkan iklim kompetitif sebagai pengejawantahan sebuah konsepsi inovasi merupakan bagian tidak terpisahkan bagi kemajuan suatu daerah. Oleh karena itu pengembangan budaya inovasi menjadi salah satu aspek budaya birokrasi yang sangat penting bagi keberhasilan reformasi birokrasi.Keberhasilan Kota Surakarta dalam mengembangkan inovasi menjadi daya tarik, meskipun sudah berganti kepemimpinan. Program inovatif terus bergulir seperti pemeliharaan kesehatan masyarakat surakarta, kartu insentif anak, digital arsip kependudukan,pelayanan KTP satu jam, dan yang lainnya. Adanya kerjasama dengan stakeholders dan masyarakat membuat program inovatif tersebut menjadi menjadi unggulan dan kebanggaan pemerintah kota Surakarta. Perencanaan program serta anggaran merupakan faktor pendukung dalam keberlangsungan program perbaikan pelayanan publik.Kata Kunci:pelayanan publik, inovasi, Kota Surakarta, good governance